Anion Directed Selective Synthesis of Supramolecular Metallocycles and Related Coordination Dimers. Issue 11 (28th January 2021) - Sturm, Lisa; Göb, Christian R.; Oppel, Iris M.
Abstract: The reaction of C 3 ‐symmetric tris ‐(2‐pyridinylene‐ N ‐oxide)triaminoguanidinium salts ([H3 L ]X) and zinc(II) in presence of thiocyanate and different carboxylate ions as co‐ligands yields in a series of different coordination compounds. Supramolecular metallocycles and carboxylate‐bridged dimers are defined by two fundamentally different binding motifs. By adjusting the co‐ligands' stoichiometry, metallocycles and carboxylate‐bridged compounds can be synthesized selectively. Furthermore, the occupation of the metallocycles with co‐ligands can also be controlled that way. Directed synthesis of these metallocycles is essential for further application in host‐guest chemistry due to their cavities and porosity in the solid state. Abstract : Selective Crystallization : A series of coordination compounds can be crystallized by the reaction of a triaminoguanidinium‐based ligand and zinc(II) in presence of thiocyanate and carboxylate ions. Supramolecular metallocycles and carboxylate‐bridged dimers are defined as two fundamentally different binding motifs. This work presents how to synthesize each selectively by adjusting the stoichiometry of thiocyanate and carboxylate ions.